Barriers and facilitators to uptake of condoms among Filipinx transgender women and cisgender men who have sex with men: A situated socio-ecological perspective. Issue 4 (2nd April 2020) - Restar, Arjee J.; Adia, Alexander; Nazareno, Jennifer; Hernandez, Laufred; Sandfort, Theo; Lurie, Mark; Cu-Uvin, Susan; Operario, Don
ABSTRACT: Transgender women (TW) and cisgender men who have sex with men (cis-MSM) are disproportionately impacted by the national HIV crisis in the Philippines, where the HIV incidence has, in large part, been attributed to condomless sex. This study sought to qualitatively examine the socio-ecological factors that contribute to low condom uptake among Filipinx TW and cis-MSM communities in Manila. Between July and August 2017, we conducted semi-structured qualitative interviews with 30 TW and cis-MSM participants ( n  = 23 and 7, respectively). We identified structural factors described by TW and cis-MSM, and noted that they varied per situation and context of: (a) friends (e.g. as condom promoters and educators), (b) schools (e.g. lack of sex education and HIV curriculum), (c) health care facilities (e.g. availability, educational programmes, and HIV testing requirement), (d) stores (e.g. placement of condoms, distance to store, and cost), and (e) church (e.g. prohibition of condom distribution programmes, and unsupportiveness). Condom-related stigma as a social factor was pervasively present across all situation or context. Our findings support the need for multilevel condom promotion interventions that are tailored per situation or context. Future research is needed to identify factors that can be leveraged for condom promotion strategies within diverse situations.